Estudio ambiental de los desechos sólidos hospitalarios (D.S.H.) que se producen en las diferentes áreas del Hospital San Vicente de Paúl del cantón Pasaje - Cruz Pérez, Carlos A. (2015)
The purpose of this work of titration consists of describing the main processes that must be followed in order to make a good solid waste management at the internal level in the institution and it´s time to develop an environmental management plan for the respective corrections, if the case deserves it.